Incidence of syphilis in the Cienfuegos province. 2013-2017 - Yoelvis Castro Bruzón; José Andrés Fuentes Soto; Yaneisy Rodríguez Cabrera; Sahily de la Caridad Ortega Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Introduction: Syphilis is one of the sexually transmitted infections which, surpassed only by HIV / AIDS, has had devastating effects on humanity and is still a health problem. Objective: To analyze the incidence of syphilis in Cienfuegos during the year 2013-2017. Method: A descriptive, retrospective study was conducted in a series of cases in PCHE (Provincial Center of Hygiene and Epidemiology of Cienfuegos), of patients diagnosed with syphilis in the period 2013 - 2017. The variables used were: age group, sex, behavior sexual, diagnostic classification by type of syphilis, risk factors and sexual orientation. Results: The most affected municipalities were Rodas and Aguada. The highest incidence was in 2013 (21.2%), although in the last two studied years there is no significant difference, with 162 patients in 2016 and 2017 (20.9%), demonstrating a high incidence of syphilis in the province. The prevailing age group was 25 to 59 years, with a total of 477 patients (61.7%), the male sex predominated with 482 patients (62.3%) over the female with 291 patients (37.6%). According to diagnostic classification by type, 395 (51%) corresponded to early latent acquired syphilis and symptomatic acquired 378 (49%). Regarding sexual behavior, it was found that heterosexuals contributed more cases, as well as non-use of the condom in terms of risk factors was the most frequent. Conclusions: There is a significant incidence of syphilis in the province. Early acquired latent syphilis prevails in males. The aim is to increase epidemiological surveillance even more in patients with risky sexual behavior.